Implementasi Pemberian Air Rebusan Daun Salam pada Keluarga Ny. R dalam Menurunkan Kadar Kolesterol - Rinawati Br Tarigan; Gilang Syahputra Siregar (Jurnal Praba : Jurnal Rumpun Kesehatan Umum, 2024)
Hypercholesterolemia is a condition where the concentration of cholesterol in the blood increases beyond normal values. One of the plants recommended for consumption by cholesterol sufferers is bay leaves. This is because bay leaves contain various active compounds such as flavonoids which can prevent the oxidation of Low Density Lipoprotein (LDL) and prevent the deposition of fat on blood vessel walls. Saponins can prevent fat absorption, increase excretion in the urine so that fat does not accumulate. This case study aims to provide an overview of implementing the provision of bay leaf boiled water in reducing cholesterol levels in Mrs. R at the health center often in Sidorejo sub-district, Medan Tembung sub-district. The type of research is descriptive with an observational approach through case studies to obtain an overview of the use of bay leaf boiled water in hypercholesterolemia sufferers. The subjects used in the case studies taken were patients with hypercholesterolemia. The instruments used in data collection were family protection observation sheets and taking action to apply boiled bay leaf water. The results of the research showed that boiled bay leaf water was effective in reducing cholesterol levels as applied by Mrs. R taken twice a day, namely morning and evening for 11 days, resulted in a decrease in cholesterol levels from 263 mg/dl to 187 mg/dl.